Community Under Stress - Vaughan, Elizabeth Head (Princeton Legacy Library, 2016)
Based on the day-to-day record of an American sociologist imprisoned for three years in a Japanese concentration camp in the seaport town of Bacolod, Negros Island, Philippines, this book deals with the relations between people in a situation of stress. An interracial group made up of many nationalities, varied economic statuses, religions, and professions gave Mrs. Vaughan ample material for her study. What is the basis of leadership in a crisis situation? What are the critical tensions? The patterns of survival and adjustment? What effect does previous cultural background have on reaction to calamity? These questions, among many others significant for social psychologists, psychiatrists, and all those concerned with human relationships, find answers here. Originally published in 1949. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These paperback editions preserve the original texts of these important books while presenting them in durable paperback editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.